Prototype system for turbidity and TDS measurement of refill drinking water using Arduino microcontroller - Saraswati, Irma; Himawan, Ganda; Wiryadinata, Romi; Ramadhani, Ahmad; Haryanto, Heri; Franata, Nauval; Yudono, Muchtar Ali Setyo; Erlindriyani, Ratu Verlaili (Jurnal Teknika, 2025)
Access to clean drinking water is critical, yet monitoring its quality in refill depots, especially in resource-limited areas, remains a challenge due to costly equipment and limited laboratory access. This work develops an Arduino Uno microcontroller-based prototype of a refill drinking water quality monitoring system based on turbidity and Total Dissolved Solids (TDS) sensors. An LED indicator serves as a visual warning and an LCD module shows real-time measurement results in the system. Five water samples from different depots underwent tests against standard Turbidity Meter and TDS Meter measuring tools. The TDS sensor fit for water quality monitoring since it displayed good performance with a low error of 0.32%–4.02% and high linearity to dissolved substance levels. Whereas the turbidity sensor is more suited for water with moderate to high turbidity, it has limited accuracy, particularly in water with low turbidity (< 5 NTU), with an error of 17%–72%. Particularly in places with limited access to labs and the Internet, this system is expected to be a sensible and affordable solution for independent refill drinking water quality monitoring. Additional development is advised to add IoT integration for remote monitoring, data storage tools, and sensitivity enhancement of the turbidity sensor.